The last shift [videorecording (DVD)] - Cohn, Andrew; Jenkins, Richard, 1947-; McGhie, Shane Paul; Randolph, Da'Vine Joy; Baker, Birgundi (Sony Pictures Home Entertainment, 2020)
On the graveyard shift at Oscar's Chicken and Fish, Stanley is retiring after 38 years and has to train his young replacement. The Boomer dropout who is leaving this career behind and the Milennial columnist who is making ends meet find ways to connect in the early hours of a quiet kitchen.